2012
DOI: 10.1002/ardp.201200140
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 1,4‐Benzothiazine: A Versatile Scaffold with Diverse Biological Properties

Abstract: 1,4-Benzothiazines are known to represent a class of medicinally important heterocyclic compounds which are extensively used in drug design. They have wide biological properties which qualify them as excellent scaffolds in therapeutic and medicinal research. Thus, many derivatives of this compound have been synthesized as target structures in novel drug development. Hence, the motivation for this present review was the known widespread application of the 1,4-benzothiazine scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…These results suggested that the nitrogen of amide functionality does not interfere in the binding with AChE. Benzothiazine derivatives have shown a diverse range of biological activities, 12 but this is the first report of AChE inhibition activity of these compounds. Antioxidant activity of the synthesized compounds was measured using DPPH and FRAP assays.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…These results suggested that the nitrogen of amide functionality does not interfere in the binding with AChE. Benzothiazine derivatives have shown a diverse range of biological activities, 12 but this is the first report of AChE inhibition activity of these compounds. Antioxidant activity of the synthesized compounds was measured using DPPH and FRAP assays.…”
Section: Resultsmentioning
confidence: 82%
“…10 Other studies on benzothiazines derivatives indicate that they possess antipyretic and analgesic activities higher than aspirin. 11,12 Studies of the structure-activity relationship of benzothiazine derivatives reveal that changing the structure of the substituent group commonly results in a change in its bioactivity. Substitution of the hydroxy group in benzothiazine derivatives enhances the effectiveness of these compounds against AD, acute neurodegenerative disorders, Pick disease, epilepsy, and ischemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Parai and colleagues prepared several 1,4-thiazine analogues and ( S )-3-methyl-1,4-benzoxazine [46]. These thiazine derivatives can be made using copper as a catalyst through the intramolecular N -aryl amination reaction mechanism on substituted 2-(2-bromo-phenylthio)ethanamines [47] that can be prepared by treating 2-bromobenzenethiol with Boc-protected amino alcohol compounds [46]. The ( S )-3-methyl-1,4-benzoxazine can be used as a reactant for the synthesis of levofloxacin which is a common quinolone antibiotic [46].…”
Section: Biological Activities Of Thiazine and Benzothiazine Derivmentioning
confidence: 99%
“…These scaffolds have been found to elicit their role, as antimicrobial [2], antitumoral [3], antidepressant [4], anti-inflammatory [5], antiarrhythmic [6], antidiabetic [7], antihypertensive [8], antirheumatic [9], antimalarial [10], anti-HIV [11], antitubercular [12] agents, antipsychotics [13], antioxidants [14], etc. Owing to the diverse applications of 1,4-benzothiazine derivatives, various synthetic routes for their preparation have been developed [15][16][17][18]. At present time, even though the disease, targets, and mechanisms of drug action are well known, there is no single systematic mode to discover a drug automatically, so identifying new drugs is a complicated, lavish, and enormously time-consuming task.…”
mentioning
confidence: 99%